The development of multisensory integration in autism spectrum disorders - Greenfield, Katie (2017)
In order to understand and interact with the world, our brains must integrate information from multiple sensory modalities to create coherent representations of scenes and events. The integration of visual, tactile and proprioceptive inputs underpins the subjective sense of self and body ownership. This, in turn, underlies the development of social processes including self-awareness, imitation and empathising, which are impaired in autism spectrum disorders (ASD). Evidence suggests that the social functioning deficits characterising ASD could contribute to atypical sensory integration underlying body representation. However, the exact mechanisms underlying sensory integration difficulties have not been specified. Moreover, it is not clear when, and how, visual, tactile and proprioceptive integration matures in typical development. This is important to establish, in order to compare how and why this integration may differ in ASD populations. This thesis firstly aimed to investigate the typical development of multisensory integration underlying body representation. Experiment One found that the ability to optimally integrate visual and proprioceptive inputs during hand localisation increases with age from very little integration in 4-year-olds to almost adult-like in typically developing 10- to 11-year-olds. Experiments Two and Three showed that sensitivity to the spatial constraints of visuo-proprioceptive integration, and sensitivity to the temporal constraints of visuo-tactile integration, develops with age in 4 to 11-year-olds. Together these studies suggest that the maturation of adult-like multisensory integration for body representation follows a protracted time course over childhood. The second aim of this thesis was to investigate the evidence for two prominent theories of atypical sensory integration underlying body representation in ASD. These are 1) an over-reliance on proprioception and 2) temporally extended sensory binding. Experiment Four examined whether trypically developing (TD) adults with a high number of autistic traits exhibit an over-reliance on proprioception. No evidence was found for this, which could indicate that atypical sensory integration is only present in individuals with a clinical diagnosis of ASD. Experiments Five and Six found evidence for temporally extended visuo-tactile integration in children with ASD, compared to TD control participants. Though no evidence was found for a fundamental over-reliance on proprioception, extended binding may have led to reduced processing of temporal synchrony over modality-specific information (i.e. proprioception). Experiment Seven and Eight found no evidence of proprioceptive over-reliance or temporally extended sensory binding in adults with ASD, relative to a TD control group. I conclude that children with ASD demonstrate temporally extended visuo-tactile binding. This represents a developmental delay rather than a life-long deficit; however, it could have a life-long impact on sensory sensitivities and social processing.